Dasar Pertimbangan Hakim Dalam Menjatuhkan Pidana Terhadap Pelaku Tindak Pidana Tidak Mematuhi Penyelenggaraan Kekarantinaan Kesehatan Di Masa Pendemi Covid-19 Berdasarkan Keputusan Presiden Nomor 11 Tahun 2020 (Studi Putusan Nomor: 110/Pid.Sus/2021/Pn Sdn) - Suherman, faizal (Universitas Semarang, 2022)
Health is a need for every human being in living his life. Health is also very important because without good health, every human being will find it difficult to carry out daily activities.